Evaluation of Plasma-microRNA320 level among Colorectal Cancer Iraqi Patients - Mohammed, Hiba Abdulameer; Kandala, Nuha Joseph (Iraqi Journal of Science, 2023)
Colorectal cancer (CRC) Patients showed different expression patterns of miRNAs which are involved in carcinogenesis in comparison to healthy controls individuals, miRNAs are involved in tumor progression and development of metastases. We investigate the expression profile of microRNA 320 and to quantify the expression level abundance among colorectal cancer patients in comparison to the healthy control group. The A total number of 60 plasma samples was collected from CRC patients along with 40 plasma samples from healthy controls and subjected to relative quantification using qPCR assay with a specified set of primers designed using stem-loop strategy. The resulting folding level revealed 2 distinguished patterns of expression; 31 samples (51.66%) were higher than the folding mean level of control (Up-regulation) and 29 samples (48.33%) were below the folding mean level (Down-regulation). The relation of folding level among healthy controls and patient groups showed a P value of 0.0001 using the Pearson Chi-square test. The Area under curve (AUC) was determined as 0.730 with a P-value of 0.0001 with a 95% confidence interval, the lower bound was 0.632 and the upper bound was 0.827.